Comparative biology of Helicoverpa armigera (Hübner) (Lepidoptera: Noctuidae) in Eucalyptus spp. (Research, Society and Development, 2020)
The Brazilian forestry sector has great importance in the economy and the sustainability of the country. With the great expansion of monoculture, and many times the proximity of agricultural and forestry plantations favors the migration or establishment of pests. The Helicoverpa armigera is a pest extremely polyphagous that occurs mainly in agricultural crops, and that casually was found feeding on eucalyptus plantations in the region of Chapadão do Sul, State of Mato Grosso do Sul, Brazil. In this study the parameters of consumption, size, and longevity of caterpillars were measured. The experimental design was completely randomized with five treatments (clones I 144; 08; Urocam VM01; AEC 1528 and artificial diet, this being a witness) and six replicates of 10 caterpillar larvae. The clones were grown in greenhouse conditions to produce leaves free of chemical plant protection products and with good nutritional status from which they have removed the sheets and supplied to the caterpillars. There was no statistical difference between the clones tested in none of the evaluated parameters. Only the artificial diet showed statistical difference concerning the size. The caterpillars fed on leaves of the clones have not completed their development, suggesting that the effect of antibiosis interfering on the biology of H. armigera not reaching status of pest.